Maintenance of intracellular Ca(2+) basal concentration in airway smooth muscle (Review) - Reyes-García, Jorge (Int J Mol Med, 2018)
In airway smooth muscle, the intracellular basal Ca(2+) concentration [(b)(Ca(2+))(i)] must be tightly regulated by several mechanisms in order to maintain a proper airway patency. The (b)[Ca(2+)](i) is efficiently regulated by sarcoplasmic reticulum Ca(2+)-ATPase 2b, plasma membrane Ca(2+)-ATPase 1 or 4 and by the Na(+)/Ca(2+) exchanger. Membranal Ca(2+) channels, including the L-type voltage dependent Ca(2+) channel (L-VDCC), T-type voltage dependent Ca(2+) channel (T-VDCC) and transient receptor potential canonical 3 (TRPC3), appear to be constitutively active under basal conditions via the action of different signaling pathways, and are responsible for Ca(2+ )influx to maintain (b)[Ca(2+)](i). The two types of voltage-dependent Ca(2+) channels (L- and T-type) are modulated by phosphorylation processes mediated by mitogen-activated protein kinase kinase (MEK) and extracellular-signal-regulated kinase 1 and 2 (ERK1/2). The MEK/ERK signaling pathway can be activated by G-protein-coupled receptors through the α(q) subunit when the endogenous ligand (i.e., acetylcholine, histamine, leukotrienes, etc.) is present under basal conditions. It may also be stimulated when receptor tyrosine kinases are occupied by the appropriate ligand (cytokines, growth factors, etc.). ERK1/2 phosphorylates L-VDCC on Ser(496 )of the β(2) subunit and Ser(1928 )of the α(1 )subunit, decreasing or increasing the channel activity, respectively, and enabling it to switch between an open and closed state. T-VDCC is also probably phosphorylated by ERK1/2, although further research is required to identify the phosphorylation sites. TRPC3 is directly activated by diacylglycerol produced by phospholipase C (PLC(β )or (γ)). Constitutive inositol 1,4,5-trisphosphate production induces the release of Ca(2+) from the sarcoplasmic reticulum through inositol triphosphate receptor 1. This ion induces Ca(2+)-induced Ca(2+) release through the ryanodine receptor 2 (designated as Ca(2+ )‘sparks’). Therefore, several Ca(2+) handling mechanisms are finely tuned to regulate basal intracellular Ca(2+) concentrations. It is conceivable that alterations in any of these processes may render airway smooth muscle susceptible to develop hyperresponsiveness that is observed in ailments such as asthma.